Influence of experimental parameters on linear, nonlinear optical and ultrafast dynamics properties of In doped ZnO nanorods. (May 2019) - Wen, Xing; Yao, Cheng-Bao; Han, Yue; Cai, Yu; Zhang, Ke-Xin; Yin, Hai-Tao; Sun, Wen-Jun
Highlights: The I and T - dependent the PL of IZO nanostructures were analyzed. The mechanism of RTPL and LTPL for IZO nanostructures is analyzed. Ultrafast nonlinear optical properties of IZO nanorods are investigated. Ultrafast carrier dynamics of IZO nanorods are investigated. Abstract: In-doped ZnO (IZO) nanorods have been successfully synthesized by chemical vapour deposition method. The structure, morphology and linear optical properties of IZO nanorods have been characterized. The excitation intensity and temperature - dependent the photoluminescence of IZO nanorods were analyzed. The nonlinear optical absorption properties were studied by using the Z-scan technique with same wavelengths at different laser pulses and energies. IZO nanorods showed two-photon absorption (TPA) mechanism at 532 nm. In the low-energy pulse regime, IZO nanorods showed TPA induced ground state saturable absorption (SA). However, with increasing the energy pulse regime, an apparent TPA induced reverse-saturable absorption (RSA) was observed. The ultrafast dynamics properties of IZO nanorods were investigated by the pump-probe technique under different laser parameters. The femtosecond transient absorption spectra show that the few decades picosecond component has been assigned to the shallow donor mixed with donor bound recombination, and the slowed components represent the decay from donor–acceptor pair recombination.